A fatal convergence: necrotizing fasciitis, critical limb ischemia, and severe secondary hyperparathyroidism in a patient with end-stage renal disease - Montelongo Sedano, Ernesto Fernando; Luna Morales, Carlos Adrián; Guillermo Baudelio, Gomez Morales (International Surgery Journal, 2025)
This case report details the clinical course of a 39-year-old female with a complex medical history, including type 2 diabetes mellitus, hypertension, and end-stage renal disease (ESRD) on hemodialysis, who presented with rapidly progressive necrotizing fasciitis (NF) of the left hand. The case exemplifies a catastrophic synergy between severe peripheral arterial disease (Rutherford 6), a polymicrobial soft tissue infection, and profound metabolic disarray secondary to renal failure. Critical laboratory findings included persistent hyperphosphatemia, hypocalcemia, and a markedly elevated parathyroid hormone (PTH) level of 270.42 pg/mL, confirming severe secondary hyperparathyroidism. This renal osteodystrophy contributed to metastatic calcification and vascular calciphylaxis, creating a non-viable tissue environment that thwarted healing and necessitated a transradial amputation. Despite surgical intervention, patient faced a high risk of contralateral limb amputation due to the underlying calcific uremic arteriolopathy, highlighting devastating systemic consequences of untreated secondary hyperparathyroidism in ESRD.